UPAYA MENINGKATAN TEKNIK LARI SPRINT 50 METER MELALUI METODE BAGIAN PADA SISWA KELAS V SD NEGERI 024 TARAI BANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR - Mukhlis Mukhlis (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research was motivated by the low sprint running technique of the PJOK students in grade V SDN 024 Tarai Bangun.This study aims to improve students' sprint running techniques in PJOK learning through the application of part methods.The subjects of this study were all fifth grade students of SDN 024 Tarai Bangun totaling 46 people, in 2017. The form of thestudy was classroom action research. The instrument of this study consisted of performance instruments and data collectioninstruments in the form of observation sheets of teacher activities and student activities. Based on the results of the researchand discussion in chapter IV, then an overview or conclusion is obtained, namely through the Part method can improve thetechnique of 50 meter student sprint. As in the first cycle it only reached an average of 63.72 with a percentage ofcompleteness reaching 23.91% or 11 students, in the first cycle it reached an average of 68 with completeness reaching60.87% or 28 students, while in cycle II it increased to average average of 74.05 with a percentage of completeness of84.78% with the number of students completing as many as 39 students.